Automation of control degrees of freedom in Aspen Hysys. (March 2022) - Safari, Ayoub
Abstract: Analysis of control degrees of freedom (CDOF) is a main step in control structure design. The CDOF in a process flow diagram (PFD) is the maximum number of manipulated material or energy streams. In this study, a CDOF analyzer is developed within Aspen Hysys simulation software by writing the scripts for enumeration of structural PFD parts i.e. boundary streams, recycle/bypass loops, circuits, holdup vessels and the engaged fluid phases in holdup vessels. The scripts are written in WinWrap Basic v10, the embedded language in Aspen Hysys. The function for identification of recycle/bypass loops is adopted from an algorithm for enumeration of chordless cycles in graph theory. Finally, the generality, reliability and ease of application of the developed analyzer are examined for analysis of several PFDs including simple units as well as the large-scale plants.